2019
DOI: 10.1002/acp.3515
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the weapon focus effect: The role of threat, unusualness, exposure duration, and scene complexity

Abstract: We examined the role of exposure duration and scene complexity on the weapon focus effect (WFE). Memory for the a mock crime was affected more by a weapon than an unusual but nonthreatening object. Threat reduced correct identifications when the event was short but not long; duration of the event did not interact with unusualness. Additionally, we found a WFE for target-absent lineup decisions, but only for the accomplice lineup, not the object-wielding perpetrator's lineup. We discuss the implications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Bayes factors indicated that the data from all our experiments provide evidence against a memory-related WFE, with evidence being moderate for Experiments 1 and 2 and strong for Experiment 3 . Moreover, several recent studies similarly found weapon presence to have no effect on or even enhance memory for at least some measures or experimental conditions (Harvey et al, 2020 ; Harvey & Sekulla, 2021 ; Mansour et al, 2019 ; Nyman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bayes factors indicated that the data from all our experiments provide evidence against a memory-related WFE, with evidence being moderate for Experiments 1 and 2 and strong for Experiment 3 . Moreover, several recent studies similarly found weapon presence to have no effect on or even enhance memory for at least some measures or experimental conditions (Harvey et al, 2020 ; Harvey & Sekulla, 2021 ; Mansour et al, 2019 ; Nyman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies found a classic WFE (Hope & Wright, 2007 ; Kim et al, 2014 ; Maass & Köhnken, 1989 ; Saunders, 2009 ), but only Hope and Wright ( 2007 ) included a gun as a weapon. In contrast, several recent European studies found that the WFE occurred only under certain conditions (Harvey & Sekulla, 2021 ; Mansour et al, 2019 ) or not at all (Harvey et al, 2020 ; Nyman et al, 2020 ). All of these more recent studies have in common that even reversed effects were found for some measures or experimental conditions.…”
mentioning
confidence: 89%
“…Trade-off effects in memory were first considered as an attentional bias in favor of central emotional elements. For instance, research on the weapon focus effect pointed out that visual focus was directed to the emotional content (i.e., the weapon), whereas peripheral details such as the individual holding the weapon were less explored ( Saunders, 2009 ; Kocab and Sporer, 2016 ; Mansour et al, 2019 ; for reviews, see Fawcett et al, 2013 ). Furthermore, emotional information had more contrast than neutral information did, leading to a pop-out effect: Salient emotional information captures attention (i.e., attentional magnets , Schmidt and Saari, 2007 ; Talmi et al, 2007 ; Hamann, 2009 ; Mennie, 2015 ; see also attentional narrowing , Winograd, 1981 ; Chipchase and Chapman, 2013 ).…”
Section: Introductionmentioning
confidence: 99%